Effectiveness and removal efficiency of certain harmful algal species using diatomite bricks - Manatad, Ma. Anita R.; Yap-Dejeto, Leni (Tacloban City Division of Natural Sciences and Mathematics, University of the Philippines Tacloban College, 2023)
Harmful algal blooms (HABs) are due to the rapid growth and accumulation of microalgae that often cause discoloration of surface waters. This phenomenon occurs worldwide affecting public health, local livelihood, and aquatic and marine organisms. Engineering solutions to adsorb HABs were introduced by spraying clay on the blooms in the aquatic ecosystems. However, this method poses a danger to the benthic communities once the clay settles to the bottom of the water. Thus, a solution is made to make clays and related materials into bricks with enough porosity to trap HABs. Raw diatomaceous earth (DE) was collected, dried, pulverized, mixed with a desired amount of water, and formed into cuboid blocks and spheres before firing. Two experimental set-ups were prepared: (1) to test the effectiveness of cuboid and spherical bricks in removing HABs cells, and (II) to compare the removal efficiency (RE) of cuboid bricks at different exposure time. Results in experiment I, showed an average removal efficiency (RE) of 37.8% for the cuboid bricks and 30.16% for the spherical bricks. Meanwhile, experiment II showed the average removal efficiency (RE) of 3.80%, 7.83%, and 24.14% in 15, 30, and 60-minute exposure time, respectively. There was a very high to perfect correlation between the number of phytoplankton populations removed and the length of time the cuboid bricks were exposed to the water sample, 0.99 to 1.00. This signifies that the device was able to absorb greater phytoplankton density and similarly, higher removal efficiency with longer time exposure.
Undergraduate thesis (B.S. in Biology) -- University of the Philippines, Tacloban.